The relationship between electromagnetic radiation of mobile phones and male infertility - a review of the literature - Patrycja Maj; Natalia Sergiel; Agata Kania; Malwina Gonet; Karolina Miszczyk; Karolina Włodarczyk-Cybulska; Piotr Mozer; Jakub Maternia; Aleksandra Serwik-Trandasir; Michał Lazar (Kazimierz Wielki University, 2023)
Introduction: In recent years, there have been more and more concerns about whether wearing mobile phones near the reproductive organs, including the testicles, may cause significant health consequences, such as sperm dysfunction, decreased semen production, impaired testicular morphology, and thus become the cause of male infertility. Determining the relationship between the electromagnetic radiation of mobile phones and infertility in men may in the future reduce the male factor in the problem of infertility of couples and thus improve the quality of life. Aim of the study: The aim of this review is to attempt to assess the impact of radiofrequency electromagnetic radiation emitted from mobile phones on male reproductive organs in the context of male fertility disorders. Materials and methods: The work was created based on the PubMed database. Articles were searched in English using the following keywords: mobile phone, testes, male infertility, electromagnetic radiation. Description of the state of knowledge: Changes in semen parameters, including reduced motility and changes in sperm morphology, have been reported in animal studies. Features of damage to living cells under the influence of oxidative stress generated by GSM radiation were also observed. Similar phenomena have been reported in vitro in human semen samples and in clinical trials in men. Summary: There are not enough studies providing strong evidence for the direct negative effect of mobile phones on male fertility. It is necessary to conduct more research in order to eliminate other factors that could potentially change the results of the analyses, as well as to standardize the test methods and the test variables.